Role of Creative Common Licenses on Open E-Books in DOAB: A Study - Dhanavandan, S. (Journal of Information and Knowledge, 2020)
This paper examines the availability of open access books and Creative Common Licenses which in the Directory Open Access Books (DOAB). The relevant data has been collected from the open access directory (http://www.openbooks.org). It reveals that among 13253, 2312 books in CC-BY, 997 books in CC-BY-NC, 4522 books in CC BY-NC-ND, 1080 CC BY-NC-SA, 188 books in CC BY-ND and 254 books in CC BY-SA categories. It is pointed out that for 3900 books license details are not mentioned in the respective sources. Out of 13253, 13052 are books and remaining 201 are book chapters.